2013
DOI: 10.4209/aaqr.2012.11.0300
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chemical and Microbial Species from Size-Segregated Indoor and Outdoor Particulate Samples

Abstract: The respirable particles in both outdoor and indoor air contain several different components that are considered to have adverse health effects; e.g., polycyclic aromatic hydrocarbons (PAHs), various metals and microbial species. In this study, size segregated particle samples were collected for chemical, microbial and toxicological analyses from the indoor and outdoor air during each season of the year. The indoor sampling was carried out in a new, detached house with a novel sampling approach. The inorganic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 70 publications
(79 reference statements)
0
27
0
Order By: Relevance
“…This view is supported by the data showing clearly their highest concentrations in the PM 10–2.5 outdoor samples in the springtime during the road dust episode [28]. In the PCA, it was found that soil related constituents in the indoor samples increased disturbances in mitochondrial activity and cytotoxicity index, while no such association was found in the samples collected outdoors.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…This view is supported by the data showing clearly their highest concentrations in the PM 10–2.5 outdoor samples in the springtime during the road dust episode [28]. In the PCA, it was found that soil related constituents in the indoor samples increased disturbances in mitochondrial activity and cytotoxicity index, while no such association was found in the samples collected outdoors.…”
Section: Resultsmentioning
confidence: 63%
“…The detailed description of the chemical composition of the samples has been presented in Sippula et al [28] and their toxicological responses reported by Happo et al [29] and collected to Additional files 1 and 2. Briefly, despite the outdoor-to-indoor-transport of the particles, it was found that indoor sources dominated the toxicological responses of the particles found inside the house.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ambient levels and composition of PM depend on the emission sources and metrological conditions [2][3][4][5][6]. PM is a complex mixture of particles of different origins with large surface areas, and the significant portion of its mass is made up of inorganic constituents (trace metals and water-soluble ions), which plays an important role in aerosol chemistry [3].…”
Section: Introductionmentioning
confidence: 99%